Urbanismo vulnerable a los procesos de remoción en masa en el municipio de San Pedro Garza García, Nuevo León (México) - Adame Rivera, Lydia Marcela (2013)
Urbanismo vulnerable a los procesos de remoción en masa en el municipio de San Pedro Garza García, Nuevo León (México).